Inter-patient variations in flow boundary conditions at middle cerebral artery from 7T PC-MRI and influence on Computational Fluid Dynamics of intracranial aneurysms. (May 2020) - Rajabzadeh-Oghaz, Hamidreza; van Ooij, Pim; Veeturi, Sricharan S.; Tutino, Vincent M.; Zwanenburg, Jaco JM.; Meng, Hui
Abstract: Background: Computational fluid dynamics(CFD) of intracranial aneurysms requires flow boundary conditions(BCs) as inputs. Patient-specific BCs are usually unavailable and substituted by literature-derived generic BCs. Therefore, we investigated inter-patient BC variations and their influence on middle cerebral artery aneurysmal hemodynamics. Method: We retrospectively collected CT angiography and 7-T Phase-Contrast(PC)-MRI data from eight middle-cerebral-artery bifurcation aneurysms to reconstruct the geometry and measure the arterial flowrates, respectively. The coefficient of variation(CoV) was calculated for the inlet flowrate and the pulsatility index(PI). The outflow split estimated by Murray's law was compared with PC-MRI measurements. For each aneurysm, we performed seven simulations: "baseline" using PC-MRI-derived BCs and the other six with changing BCs to explore the influence of BC variations on hemodynamics. Results: From PC-MRI, the inlet flowrate was 1.94 ± 0.71 cm 3 /s(CoV = 36%) and PI was 0.37 ± 0.13(CoV = 34%). The outflow split estimated by Murray's law deviated by 15.3% compared to PC-MRI. Comparing to " baseline" models, ±36% variations in inlet flowrate caused −61% to +89% changes in time-averaged wall shear stress(WSS), −37% to +32% in normalized WSS(NWSS; by parent-artery), and −42% to +126% in oscillatory shear index(OSI). The ±34% variations in PI caused, −46% to +67% in OSI. Applying ±15% variations in outflow split led to inflow jet deflection and −41% to +52% changes in WSS, −41% to +47% in NWSS, and −44% to +144% in OSI. Conclusion: Inflow rate and outflow split have a drastic impact on hemodynamics of intracranial aneurysms. Inlet waveform has a negligible impact on WSS and NWSS but major impact on OSI. CFD-based models need to consider such sensitivity.